Can Helicopters Solve the Transport Dilemma for Patients With Symptoms of Large-Vessel Occlusion Stroke in Intermediate Density Areas? A Simulation Model Based on Real Life Data - Behrndtz, Anne; Beare, Richard; Iievlieva, Svitlana; Andersen, Grethe; Mainz, Jeppe; Gude, Martin; Ma, Henry; Srikanth, Velandai; Simonsen, Claus Z.; Phan, Thanh (Frontiers in Neurology, 2022)
Background: This modeling study aimed to determine if helicopters may optimize transportation of patients with symptoms of large vessel stroke in “intermediate density” areas like Denmark, by bringing them directly to comprehensive stroke center. Methods: We estimated time to treatment for patients requiring endovascular therapy or intravenous thrombolysis under four configurations: “drip and ship” with and without helicopter and “bypass” with and without helicopter. Time delays, stroke numbers per municipality, and helicopter dispatches for four helicopter bases from 2019 were obtained from the Danish Stroke and Helicopter Registries. Discrete event simulation (DES) was used to estimate the capacity of the helicopter fleet to meet patient transport requests, given the number of stroke codes per municipality. Results: The median onset-to-needle time at comprehensive stroke center (CSC) for the bypass model with helicopter was 115 minutes (interquartile range (IQR): 108, 124); the median onset-to-groin time was 157 minutes (IQR: 150,166). The median onset-to-needle time at the primary stroke center (PSC) by ground transport was 112 minutes (IQR: 101, 125) and the median onset-to-groin time when primary transport to the PSC was prioritized was 234 minutes (IQR: 209, 261). Linear correlation between travel time by ground and the number of patients transported by helicopter (rho = 0.69, p< 0.001) indicated that helicopters are being used to transport more remote patients. DES demonstrated that an increase in helicopter capture zone by 20 minutes increased the number of rejected patients by only 5%. Conclusions: Our model calculations suggest that using helicopters to transport stroke patients directly to the CSC in intermediate density areas markedly reduce onset-to-groin time without affecting time to thrombolysis. In this setting, helicopter capacity is not challenged by increasing capture zone.